Childhood cancer predisposition syndromes—A concise review and recommendations by the Cancer Predisposition Working Group of the Society for Pediatric Oncology and Hematology. Issue 4 (7th February 2017) - Ripperger, Tim; Bielack, Stefan S.; Borkhardt, Arndt; Brecht, Ines B.; Burkhardt, Birgit; Calaminus, Gabriele; Debatin, Klaus‐Michael; Deubzer, Hedwig; Dirksen, Uta; Eckert, Cornelia; Eggert, Angelika; Erlacher, Miriam; et al.
Abstract : Heritable predisposition is an important cause of cancer in children and adolescents. Although a large number of cancer predisposition genes and their associated syndromes and malignancies have already been described, it appears likely that there are more pediatric cancer patients in whom heritable cancer predisposition syndromes have yet to be recognized. In a consensus meeting in the beginning of 2016, we convened experts in Human Genetics and Pediatric Hematology/Oncology to review the available data, to categorize the large amount of information, and to develop recommendations regarding when a cancer predisposition syndrome should be suspected in a young oncology patient. This review summarizes the current knowledge of cancer predisposition syndromes in pediatric oncology and provides essential information on clinical situations in which a childhood cancer predisposition syndrome should be suspected.